Ceramic-on-Ceramic Bearings in Total Joint Arthroplasty. Part 3 - Zazirnyi, I.M. (TERRA ORTHOPAEDICA, 2023)
Summary. Total hip arthroplasty (THA) currently provides durable long-term outcomes, but osteolysis secondary to polyethylene wear debris remains a fundamental cause of aseptic loosening and revision. Conventional polyethylene failed to provide a suitable bearing for young active patients requiring joint replacement because of the significant demands they place on such bearings. Strategies to reduce friction and wear debris lead to the development of ceramic bearings in THA. The next decade is unlikely to see a paradigm shift in the materials used for THA. Instead, the challenges will be aimed at improving surgical technique in terms of component orientation to improve reproducibility and achieve superior patient outcomes. The optimum bearing surface is one with very low wear rates, a low coefficient of friction, scratch resistance, and is biologically inert. It is also one that can safely accommodate larger femoral head sizes to minimize dislocation rates without damaging the taper junction. Such a material already exists with modern ceramic bearings.